"Sex passport" obligation for female athletes. Consideration and criticisms on 364 subjects - Vignetti, P.; Rizzuti, A.; Bruni, L.; Tozzi, M. C.; Marcozzi, P.; Tarani, L. (International Journal of Sports Medicine, 1996)
In Ancient Greece determination of sex was made by direct observation of the all-male athletes participating in the Olympic Games. In 1966 the International Olympic Committee (I.O.C.) established that female athletes must submit to a complete physical examination before each international competition. In 1968 they further established that each female participant be granted a "Sex Passport" based upon the findings of a medical and gynaecological examination as well as chromosomal sex determination. The authors, whose department has been responsible for granting Sex Passports for more than 20 years, examined 364 female athletes aged 16 to 29 years using I.O.C. criteria. They found three chromatic-negative cases (0.8%). The present work indicates several scientific shortcomings of the current I.O.C. examination criteria, illustrates three chromatin-negative cases, their consequences and proposed a return to original criteria for examination except in doubtful cases.